2021
DOI: 10.1016/j.msea.2020.140452
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure study of cold rolled Al0.32CoCrFeMnNi high-entropy alloy: Interactions between recrystallization and precipitation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Extensive work regarding the influence of thermo-mechanical processing and thermal treatments in these multiphase fcc-based HEAs is currently in progress as a way for maximizing their strengths [6][7][8][9][10][11][12]. On the contrary, less attention has been dedicated to thermomechanical processing of fcc-based single-phase HEAs because their mechanical properties are lower than those of multiphase fcc-based HEAs.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive work regarding the influence of thermo-mechanical processing and thermal treatments in these multiphase fcc-based HEAs is currently in progress as a way for maximizing their strengths [6][7][8][9][10][11][12]. On the contrary, less attention has been dedicated to thermomechanical processing of fcc-based single-phase HEAs because their mechanical properties are lower than those of multiphase fcc-based HEAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, various types of complex phases such as σ , μ, and Laves are also found that can affect the strength and ductility of HEAs [6][7][8]. Appropriate processing routes can be utilised to optimise the dimension, distribution, and shape of these brittle and hard precipitates to reach the desired mechanical properties [9,10].…”
Section: Introductionmentioning
confidence: 99%